ALFIERI IN VIAGGIO CON MONTAIGNE: LA RICERCA DI UN'IDENTITÀ INTERIORE (Italiano LinguaDue, 2025)
Il seguente saggio intende indagare due aspetti importanti nella vita dell’autore: i viaggi, considerati soprattutto da un punto di vista conoscitivo e metafisico, e la lettura dei Saggi di Montaigne. Incrociando fra loro questi due elementi, le loro circostanze e le loro reciproche influenze, l’articolo vuole evidenziare come questi aspetti siano basilari per la conversione interiore di Alfieri ai fini della nascita vera e propria della vocazione poetica.   Alfieri travelling with Montaigne: the search for an inner identityThe following essay intends to investigate two important aspects in the author’s life: his travels, considered mainly from a cognitive and metaphysical point of view, and his reading of Montaigne’s Essays. Cross-referencing these two elements, their circumstances and mutual influences, the article aims to highlight how these aspects are basic to Alfieri's inner conversion for the purpose of the actual birth of the poetic vocation.